The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12705/662.5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships and generic re‐arrangements in “South Andean Loasas” (Loasaceae)

Abstract: Loasaceae, a mostly American group, is one of the largest families of Cornales. In spite of considerable progress over the last 20 years, the relationships of some clades remain controversial, especially in the “South Andean Loasas” (SAL—Blumenbachia, Caiophora, Loasa, Scyphanthus). The present study addresses the phylogenetic relationships in SAL employing four plastid markers (rps16, trnL‐trnF, trnS‐trnG, matK) and ITS and aims at resolving the systematics and evolution of the group. Sequences obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…Molecular studies have largely confirmed earlier systematic re-arrangements based on morphology (e.g. 53 ), and the phylogeny of the group can be considered as well-resolved 54 56 . In spite of its relatively moderate number of species, the family is morphologically highly diversified (Fig.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Molecular studies have largely confirmed earlier systematic re-arrangements based on morphology (e.g. 53 ), and the phylogeny of the group can be considered as well-resolved 54 56 . In spite of its relatively moderate number of species, the family is morphologically highly diversified (Fig.…”
Section: Introductionsupporting
confidence: 65%
“…The PCR amplification and sequencing protocols follow Acuña et al . 56 . Sequences were assembled in Geneious v. 8.0.1 84 using the default De Novo assemble settings.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed sequences from four plastid regions: trn L– trn F, mat K, the trn S– trn G intergenic spacers and the rps 16 intron. These have proved to be informative to infer the phylogenetic relationships in Loasoideae (Weigend et al 2004; Hufford et al 2005; Weigend and Gottschling 2006; Acuña et al 2017). Sequences were newly generated for this study or for previously published research by our working group (Acuña et al 2017, 2018; Henning et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Our sampling for the molecular study included 81 species (ca. 25%) of Loasaceae, plus six asterids which broadly mirrored sampling from Acuña et al (2017). All currently recognized genera and most major infrageneric clades of Loasaceae subfamily Loasoideae were included.…”
Section: Molecular Studiesmentioning
confidence: 99%
“…Volubiles and ser. Acaules from Loasa s.s. into the new genus Grausa Weigend & R.H. Acuña (Acuña et al, 2017) Acuña], but also the acaulescent, high-Andean G. lateritia. As Loasa acaulis was considered a synonym of L. lateritia it was implicitly assumed that it was also part of Grausa, however this has never been tested using phylogenetic (molecular or otherwise) evidence.…”
Section: Introductionmentioning
confidence: 99%